2020
DOI: 10.1093/toxres/tfaa023
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking analyses of CYP450 monooxygenases of Tribolium castaneum (Herbst) reveal synergism of quercetin with paraoxon and tetraethyl pyrophosphate: in vivo and in silico studies

Abstract: Abstract Pest management in stored grain industry is a global issue due to the development of insecticide resistance in stored grain insect pests. Excessive use of insecticides at higher doses poses a serious threat of food contamination and residual toxicity for grain consumers. Since the development of new pesticide incurs heavy costs, identifying an effective synergist can provide a ready and economical tool for controlling resistant pest populations. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Inhibition of alpha amylase activity by an allergenic protein Ric C1 & Ric C3 from Ricinus communis was reported by Nascimento et al (2011). Ghaffar et al (2020) also revealed the inhibitory effect of quercetin, paraoxon and tetraethyl pyrophosphate on enzyme CYP450 isoenzyme of Tribolium casteneum. Another study by Gupta et al (2023) on insecticidal and detoxification activity of Acorus calamus and Lavandula angustifoli revealed that these plant extracts have the potential to inhibit Glutathione S Transferase activity of C. chinensis.…”
Section: Resultsmentioning
confidence: 88%
“…Inhibition of alpha amylase activity by an allergenic protein Ric C1 & Ric C3 from Ricinus communis was reported by Nascimento et al (2011). Ghaffar et al (2020) also revealed the inhibitory effect of quercetin, paraoxon and tetraethyl pyrophosphate on enzyme CYP450 isoenzyme of Tribolium casteneum. Another study by Gupta et al (2023) on insecticidal and detoxification activity of Acorus calamus and Lavandula angustifoli revealed that these plant extracts have the potential to inhibit Glutathione S Transferase activity of C. chinensis.…”
Section: Resultsmentioning
confidence: 88%
“…The molecular docking technique has utilized to mimic the interaction between a small molecule and a protein at the atomic level, providing insight into the underlying efficiency involved and allowing scientists to define the binding energy of small molecules in the binding region of target proteins [65][66][67]. The docking computations were conducted with the help of the program AutoDock (PyRx), and the binding energy of the peptide was determined.…”
Section: Molecular Docking Against Targeted Receptormentioning
confidence: 99%
“…In general, cytochromes are very often recruited within the body to detoxify various toxicants and/or xenobiotics [ 10 , 68 ]. Therefore, their effect on OPCs can be nonspecific, and their activity can be greatly reduced in comparison with other substrates or even inhibited by OPC alone [ 69 ] or in combination with other substances [ 70 ]. Nevertheless, compounds of a wide subclass of OPCs containing P=S bond (e.g., parathion [ 71 ], phosmet [ 72 ], diazinon [ 73 ], etc.)…”
Section: Cytochromementioning
confidence: 99%